Investigating the heterogeneity of alkylating agents' efficacy and toxicity between sexes: A systematic review and meta‐analysis of randomized trials comparing cyclophosphamide and ifosfamide (MAIAGE study). Issue 8 (23rd January 2017) - Fresneau, Brice; Hackshaw, A.; Hawkins, D.S.; Paulussen, M.; Anderson, J.R.; Judson, I.; Litière, S.; Dirksen, U.; Lewis, I.; van den Berg, H.; Gaspar, N.; Gelderblom, H.; et al.
Abstract: Background: A marginal interaction between sex and the type of alkylating agent was observed for event‐free survival in the Euro‐EWING99‐R1 randomized controlled trial (RCT) comparing cyclophosphamide and ifosfamide in Ewing sarcoma. To further evaluate this interaction, we performed an individual patient data meta‐analysis of RCTs assessing cyclophosphamide versus ifosfamide in any type of cancer. Methods: A literature search produced two more eligible RCTs (EICESS92 and IRS‐IV). The endpoints were progression‐free survival (PFS, main endpoint) and overall survival (OS). The hazard ratios (HRs) of the treatment‐by‐sex interaction and their 95% confidence interval (95% CI) were assessed using stratified multivariable Cox models. Heterogeneity of the interaction across age categories and trials was explored. We also assessed this interaction for severe acute toxicity using logistic models. Results: The meta‐analysis comprised 1, 528 pediatric and young adult sarcoma patients from three RCTs: Euro‐EWING99‐R1 (n = 856), EICESS92 (n = 155), and IRS‐IV (n = 517). There were 224 PFS events in Euro‐EWING99‐R1 and 200 in the validation set (EICESS92 + IRS‐IV), and 171 and 154 deaths in each dataset, respectively. The estimated treatment‐by‐sex interaction for PFS in Euro‐EWING99‐R1 (HR = 1.73, 95% CI = 1.00–3.00) was not replicated in the validation set (HR = 0.97, 95% CI = 0.55–1.72), without heterogeneity across trials ( P = 0.62). In the pooled analysis, the treatment‐by‐sex interaction was not significant (HR = 1.31, 95% CI = 0.89–1.95, P = 0.17), without heterogeneity across age categories ( P = 0.88) and trials ( P = 0.36). Similar results were observed for OS. No significant treatment‐by‐sex interaction was observed for leucopenia/neutropenia ( P = 0.45), infection ( P = 0.64), or renal toxicity ( P = 0.20). Conclusion: Our meta‐analysis did not confirm the hypothesis of a treatment‐by‐sex interaction on efficacy or toxicity outcomes.